Digital Inequity and Knowledge Divide among Intersectional Identities - Kumari, Shivangi; Singha, jagriti; Gardia, Alok (JOURNAL OF INDIAN EDUCATION, 2024)
In the 21st century, the development, distribution, and utilisation of knowledge are crucial and digital equity is a prerequisite to building an egalitarian knowledge society. Nearly 9 per cent of students enrolled in any course had access to a computer with the internet, according to NSS data. Only 25 per cent of the total number of registered students had access to the internet via any type of gadget. More than 40 per cent of students in the Northeast region of India were devoid of any digital tools to attend online classes during COVID-19, according to the NAS report 2021. According to ‘India Inequality Report 2022: Digital Divide’ released by NGO Oxfam India, barely one-third of Internet users are women. The existing global digital inequity widens the knowledge divide between the haves and have-nots. As a result, sociotechnical discrepancies are often magnified leading to the emergence of diverse forms of social exclusion, marginalisation and vulnerabilities. Intersectional discrimination acknowledges social disadvantages result from the intersection of multiple social identities. The purpose of the study is to reveal the variations in digital accessibility across different intersectional identities and identify the potential barriers in our schools and society that impede students’ legitimate digital access. The study has indicated that access to digital infrastructure and devices has created a significant disparity between students from different socio-economic and caste groups, making online learning difficult for many.